(3eHGOF EOGQI GdCYeGd (B:s [(3GdJNWjW,GdJfXje,GdJhLjg,GdbjGOI,GdQbGHI(B] /s - (3ThjM,eMeOs ((3GdLRGFQ(B: s (3LShQ(B, s, 2015)
(3GdeaGgje GdGOGQjI , CSGSjGJ GdJNWjW h CfhGY h JbSjeGJ GdJNWjW h NWhGJg , Gdbje GdCNdGbjI h GdJNWjW, CSGSjG GdJfXje h CYOGO h JUeje Gdgjcd GdJfXjej h GdSdWI h GdeSDhdjI h VhGHWgG GdCNdGbjI h GdeHGOF h Gdbje GdCNdGbjI ddJfXje , JYQja GdJhLg h CSSg h CNdGbg h GdJMajR h CfhGYg h Gdbje GdCNdGbjI h GdGJUGd h Gdbje GdCNdGbjI , eaghe GdbjGOI GdGOGQjI h CfeGWgG h ebheGJ h TQhW GdbjGOI GdGOGQjI , eaghe GdQbGHI h CgejJgG h CfhGYgG h NWhGJgG h Gdbje GdGNdGbjI ddQbGHI(B.s
(3eQGLY U(B.213s
Keywords: (3EOGQI GdCYeGds